A guerra nos fones de ouvido: desinformação, manipulação de discursos e mídias no conflito russo-ucraniano - Ferreira, Artur de Oliveira (2024)
This master's degree aimed to contextualize the role of journalistic podcasts as a prominent technological medium in covering the conflict between Russia and Ukraine in Eastern Europe, playing a significant role in combating the spread of misinformation on social networks. For this purpose, the programs "Petit Journal," produced independently by professors Daniel Souza and Tanguy Baghdadi, and "O Mundo em Meia Hora" from Rádio CBN (Central Brasileira de Notícias), were selected for analysis. This research also employs theoretical tools from Discourse Analysis. The main authors consulted for the formulation of this research are scholars Henry Jenkins, Eduardo Vicente, Marcelo Kischinhevsky, Pablo de Assis, Lucio Luiz, and Orlandi. The final considerations point to a very robust development of the national journalistic podcast genre, and these programs have currently become a reference for part of the readers, listeners, and viewers, requiring more in-depth analyses and expert commentary, as is the case with the Russia-Ukraine war